Corrigendum to: Biomass modification using cationic surfactant cetyltrimethylammonium bromide (CTAB) to remove palm-based cooking oil (Journal of Chemistry (2018) 2018 (5059791) DOI: 10.1155/2018/5059791) - Amira Satirawaty, Mohd PauzanI; Normala, Ahad (Hindawi Limited, 2019)
In the article titled "Biomass Modification Using Cationic Surfactant Cetyltrimethylammonium Bromide (CTAB) to Remove Palm-Based Cooking Oil" [1], the grant details were missing from the Acknowledgments section as follows: "Thanks are extended to the Universiti Malaysia Sarawak for the funding and facilities provided." Thus, the Acknowledgments section should be updated as follows: "This study was supported by the research grant from the Ministry of Higher Education, Malaysia, under the Research Acculturation Grant Scheme (RAGS) with Grant number RAGS/ST/01(1)/932/2012(33). The authors wish to thank Universiti Malaysia Sarawak for the facilities provided."